Effects of silver diffusement on TiO2-B2O3 nanocomposite sensor towards hydrogen sensing - Mohd Chachuli, Siti Amaniah; Hamidon, Mohd Nizar; Ertugurl, Mehmet; Mamat, Md. Shuhazlly; Coban, Omer; Shamsudin, N.H.; Arith, Faiz (Taylor and Francis Ltd., 2024)
Various finger dimensions of interdigitated electrodes in TiO2-B2O3 nanocomposite sensors were proposed in this study. To study the silver diffusement effect on the hydrogen sensing characteristics at different operating temperatures. The result showed that some of the silver particles diffused to the surface of the TiO2-B2O3 nanocomposite sensor after the annealing process at 500°C. The amount of silver particles diffused into the TiO2-B2O3 surface was contributed by the finger dimension of the interdigitated electrode used in the nanocomposite sensor. The results revealed that the structure of interdigitated electrodes in T65 nanocomposite sensor enhanced the performance at low hydrogen concentrations with response values were approximately 4.78, 11.47, 14.47, 16.58, and 20.00 for 100 ppm, 300 ppm, 500 ppm, 700 ppm, and 1000 ppm, respectively, at the optimum operating temperature of 200°C. The activation energy for all nanocomposite sensors was approximately in the range of 40–70 kJ/mol.